Executive coaching with backbone and heart - O'Neill, Mary Beth (Jossey-Bass Publishers, 2000)
Includes bibliographical references (p. 235-236) and index; 3 parts: Core concepts: the coach's stance; the four phases of coaching; special applications; Quỹ Châu Á